Solvent Interactions and Solvation Models in the Oxidation of Benzyl Alcohol by Quinolinium Dichromate - Manikyamba, P. (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of benzyl alcohol by quinolinium dichromate has been studied in different pure protic and aprotic solvents. The rate data is correlated with different solvation parameters using linear multiple regression analysis. From the regression coefficients, information on the solvent-solute interactions is obtained and the solvation models are proposed.